Policies, Programs, and Activities of the Department of the Interior.: hearings before the United States House Committee on Interior and Insular Affairs, Eighty-Ninth Congress, first session. - United States. (U.S. G.P.O., 1965)
Committee Serial No. 1
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part VIII
Committee Serial No. 1
Keywords: Saline water conversion / United States.